2021
DOI: 10.1186/s12870-021-02946-2
|View full text |Cite
|
Sign up to set email alerts
|

Mass propagation of Juniperus procera Hoechst. Ex Endl. From seedling and screening of bioactive compounds in shoot and callus extract

Abstract: Background Juniperus procera Hoechst. ex Endl. is a medicinal tree in Saudi Arabia, primarily in the Enemas region, but it is locally threatened due to die-back disease and difficulties regarding seed reproduction (seed dormancy and underdeveloped embryonic anatomy, and germination rate < 40%). Hence, the alternative methods for reproduction of Juniperus procera are really needed for conservation and getting mass propagation for pharmaceutical uses. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…Moreover, it has been reported that ferruginol inhibits the growth of cancer cells ( González et al, 2014 ). Recently, we detected ferruginol in the different parts of J. procera using GC-MS, DART-MS, and HPLC ( Salih et al, 2021a , b ; Figure 8A ), and it is a dominant compound in different parts of this plant. This study separated ferruginol and identified it using HPLC, with ferruginol standard ( Figures 8B,C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been reported that ferruginol inhibits the growth of cancer cells ( González et al, 2014 ). Recently, we detected ferruginol in the different parts of J. procera using GC-MS, DART-MS, and HPLC ( Salih et al, 2021a , b ; Figure 8A ), and it is a dominant compound in different parts of this plant. This study separated ferruginol and identified it using HPLC, with ferruginol standard ( Figures 8B,C ).…”
Section: Resultsmentioning
confidence: 99%
“…7 g/L of agar was added, and the pH was maintained at 5.7. Following the protocol, we recently reported ( Salih et al, 2021a ). Next, different concentrations of biogenic AgNPs (0.0, 5, 10, 20, and 50 mg/L) were added to the WPM before sterilizing at 121°C for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…Ex Endl. (Salih et al, 2021), Ficus religiosa (Hesami et al, 2018), and Securidaca longipedunculata (Lijalem and Feyissa, 2020). Bisht et al (2012) investigated the in vitro propagation of Polygonatum verticillatum and suggested that the favorable impact of cytokinin and auxin combination is due to increased RNA synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Since the ethanol extract from seed contained a higher value of phenolic compounds, it was submitted to GC-MS analysis to identify the phytochemical compounds and resulted in very important bioactive compounds such as ferruginol, phenanthrene, and n-hexadecanoic acid related to phenolic compounds (Table 5 and Figure 5). The bioactive compounds in the leaf extract of J. procera were screened previously [43]; however, some variation has been recorded between the seed and leaf extract (Table 5) in the screened bioactive compounds. Moreover, different parts of the plant occupy a pool of bioactive compounds containing potential chemical groups [30].…”
Section: Gc-ms Analysis Of Seed and Leaf Extract Of Juniperus Proceramentioning
confidence: 99%
“…The injection temperature was 280 • C and the column temperature was adjusted to 300 • C. Helium gas was used as the carrier with a flow rate of 1 mL/min. The electron ionization energy was 70 eV while the GC-MS analysis leaf extract of J. procera was undertaken and published recently [43].…”
Section: Preparation Of Plant Materials For Gc-ms Analysismentioning
confidence: 99%